For a formal theory of enunciation and an extended theory of the image - Marsciani, Francesco (E|C, 2020)
Starting from the title, I will try to account for the intentions it expresses in consideration of the two poles it exposes: a formal theory of enunciation, on the one hand, and an extended theory of the image, on the other. The value I entrust to the term "theory" that recurs in the title is to indicate, rather than develop, the necessary scope, indispensable in my opinion, of a theoretical (I would say constructive) dimension of the reflections that we are still allowed to make on our two objects - enunciation and image - so alive.